2021
DOI: 10.3390/ijms22158101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bone Grafting Materials and Mesenchymal Stem Cells on Bone Regeneration: A Micro-Computed Tomography and Histomorphometric Study in a Rabbit Calvarial Defect Model

Abstract: This study evaluated the new bone formation potential of micro–macro biphasic calcium phosphate (MBCP) and Bio-Oss grafting materials with and without dental pulp-derived mesenchymal stem cells (DPSCs) and bone marrow-derived mesenchymal stem cells (BMSCs) in a rabbit calvarial bone defect model. The surface structure of the grafting materials was evaluated using a scanning electron microscope (SEM). The multipotent differentiation characteristics of the DPSCs and BMSCs were assessed. Four circular bone defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…LAC-2017-0514). DPSCs were isolated from freshly extracted teeth, as described previously [ 5 , 8 , 40 ]. In brief, incisors were extracted from different rabbits, and the dental pulp tissues were carefully harvested.…”
Section: Methodsmentioning
confidence: 99%
“…LAC-2017-0514). DPSCs were isolated from freshly extracted teeth, as described previously [ 5 , 8 , 40 ]. In brief, incisors were extracted from different rabbits, and the dental pulp tissues were carefully harvested.…”
Section: Methodsmentioning
confidence: 99%
“…The block bone has a rigid three-dimensional structure and provides space for the migration of osteogenic cells and new bone formation. The higher values of BV and TbTh are considered new bone formation and new bone regeneration [31,32]. The results of BV and ThTb indicated that the block bone was a more suitable scaffold than the particle bone as a BMP carrier.…”
Section: Discussionmentioning
confidence: 99%
“…In a typical carbodiimide reaction, the coupling reagent (i.e., EDC, DCC, DIC, etc.) is added in excess to ensure high conjugation efficiency (Pan et al, 2012;Biju, 2014;Wang et al, 2014;Gandhi et al, 2016;Zhang et al, 2016;Kuo et al, 2017;Palmieri et al, 2018;Shipunova et al, 2018;Wang et al, 2018;Elzahhar et al, 2019;Lim et al, 2019;Shiu et al, 2021;Wright et al, 2021), which leads to a highly activated carboxylate environment in the reaction medium. All primary amines within the peptide can participate in nucleophilic addition-elimination regardless of relative reactivities in such environments.…”
Section: Indirect Peptide Quantification Assays Provide Misleading Co...mentioning
confidence: 99%